Sensory-processing sensitivity versus the sensory-processing theory: Convergence and divergence - Turjeman-Levi, Yaara; Kluger, Avraham N. (Frontiers in Psychology, 2022)
Two individual-difference theories focus on sensory sensitivity: one emanating from psychology—sensory-processing-sensitivity (SPS); and one from occupational therapy—sensory processing theory (SP). Each theory is coupled with its measure: the highly-sensitive-person scale (HSPS) and the adolescent adult sensory profile (ASP). The constructs of both theories were claimed to be independent of neuroticism. To assess the convergence of these measures, we recruited participants from a general population and a Facebook Group dedicated to people high in SPS. The participants, N = 1,702 Mage = 26.9 (66.7% female), answered the HSPS, ASP, and neuroticism questionnaires. We subjected the HSPS and the APS to exploratory graph analysis. To assess the divergence of these measures from neuroticism, we performed meta-analyses. We also used a subsample obtained in an unrelated study, N = 490, to correlate HSPS and APS with the Big Five and additional measures. The results suggested that (a) the latent structure of these measures conforms to the theories only partially, (b) some of the sub-scales of these two measures correlated highly, r = 0.63, but low enough to suggest divergence, (c) both differentially predict membership in a Facebook group, and (d) both are not isomorphic with neuroticism. We concluded that HSPS primarily measures the emotional reaction to sensory stimulation, whereas ASP the behavioral reactions. We offer shorter yet reliable measures for both theories.